2021
DOI: 10.3389/fsufs.2021.616033
|View full text |Cite
|
Sign up to set email alerts
|

Response of Peanut Varieties to Phosphorus and Rhizobium Inoculant Rates on Haplic Lixisols of Guinea Savanna Zone of Ghana

Abstract: Peanut forms a major component of the predominantly cereal-based farming systems in Northern Ghana. However, yields are low, prompting the need to evaluate the effects of phosphorus (PR) and rhizobium inoculant (IR) rates on growth, nodulation, and yield of peanut varieties. On-station and on-farm experiments were conducted to determine the interaction effects of three P rates (0, 30, and 60 kg P2O5/ha), three IR rates (0, 3, and 6 g/kg seed), and two peanut varieties [Chinese and Nkatie Savannah Agricultural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…This result suggested that P limitation is a possible explanation for the slight effects of rhizobial inoculation, although the experiment was not designed to test this hypothesis. Indeed, in Ghana, the influence of P fertilization on groundnut yields was demonstrated by Asante et al (2020) using the USDA3456 and BR3267 strains and by Yaro et al (2021) using the BR3267 strain.…”
Section: Values Are Means Of Five Repetitionsmentioning
confidence: 99%
“…This result suggested that P limitation is a possible explanation for the slight effects of rhizobial inoculation, although the experiment was not designed to test this hypothesis. Indeed, in Ghana, the influence of P fertilization on groundnut yields was demonstrated by Asante et al (2020) using the USDA3456 and BR3267 strains and by Yaro et al (2021) using the BR3267 strain.…”
Section: Values Are Means Of Five Repetitionsmentioning
confidence: 99%